Desmoplastic sebaceoma arising from nevus sebaceus: a new variant. (2nd April 2014) - Chuang, Huei‐Chieh; Kao, Pei‐Han; Huang, Yen‐Lin; Lee, Li-Yu; Kuo, Tseng‐tong
<x xml:space="preserve">Abstract</x> Nevus sebaceus is known to have the potential to develop into various secondary tumors. We observed a sebaceoma arising from a nevus sebaceus excised from the left cheek of a 51‐year‐old woman. This sebaceoma showed desmoplastic change similar to that observed in desmoplastic trichoepithelioma and desmoplastic trichilemmoma. This heretofore undescribed desmoplastic variant of sebaceoma should not be mistaken for invasive sebaceous carcinoma.